Some characteristics of the rainfall regime at Douala, Cameroun - Mbele-Mbong, Samuel, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 1972)
This study is a progress report on 'Water resources of Africa, the cases of Cameroun and Ghana'.
Water resources of Africa, the cases of Cameroun and Ghana
Keywords: Rain and rainfall -- Cameroon -- Douala